Formulation and Evaluation Of Black Garlic (Allium Sativum L.) Lozenges As An Antioxidant Supplement - Norisca Aliza Putriana; Efri Mardawati; Yoga Windu Wardhana; Ismiatun Ismiatun; Anting Wulandari; Dwi Wahyudha Wira; Nanang Masruchin (Indonesian Journal of Pharmaceutics, 2022)
Free radicals are species of reactive chemical compounds that can cause degenerative diseases. Antioxidants work to deactivate free radicals by binding to these radicals to stabilize the radicals. One of the plants that contain antioxidants is black garlic. This study aimed to obtain the best formula from the preparation of lozenges of black garlic extract using the wet granulation method as an antioxidant supplement. The formula optimization was carried out using a statistical approach with a two-level factorial method using expert design software. The lozenges formula was made using wet granulation method. The granules and tablets were evaluated for its characteristic. Besides, the levels of polyphenols and antioxidant activity of the extracts and lozenges were also determined. The best formula is F2 obtained from a ratio of gum arabic and starch pregelatin of 3: 5 with a desirability value of 0.922. The Evaluation of black garlic extract granules is eligible, including the moisture content of 2.04%, an excellent flow rate is 18.3 g/s, and good compressibility of 9%. The uniformity of lozenge weight obtained is eligible, which is 3%. The hardness and disintegration time of  9.1 kg and 11.28 minutes, respectively. Meanwhile, the antioxidant activity of the extract and lozenges was 263 µg/mL and 323.9 µg/mL, respectively. The best formula obtained is with 3% gum arabic and 5% starch pregelatin.Keywords: Antioxidant, Black Garlic, Design expert, Lozenges